Analisis Strategi Pemasaran Chatime Melalui Kolaborasi Dengan JKT 48 Dalam Meningkatkan Penjualan - Audy Saomramadhan; Abdullah Abbas; Erwin Permana (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The contemporary beverage business in Indonesia is experiencing rapid growth, driven by lifestyle changes and the influence of social media. Competition in this industry is very tight, so collaboration is the key to survival. Chatime has successfully maintained its position as the most popular contemporary beverage brand through collaboration with the music group JKT-48. This study aims to analyze Chatime's marketing strategy through collaboration with JKT 48 in increasing sales and consumer appeal. This study was conducted using a descriptive qualitative approach. Research data were obtained from the results of observations and digital reviews as well as support from various secondary literature. The results of the study indicate that collaboration with JKT48 is a successful marketing strategy, especially during the Senbatsu Sousenkyo (SSK) event, which increases sales. Chatime's collaboration with JKT48 has proven effective in increasing sales through the launch of an attractive collaboration menu, the creation of exclusive merchandise, and holding events for joint promotions. This influencer marketing strategy has succeeded in utilizing the loyalty of JKT48 fans to encourage purchases of Chatime products. The author suggests that Chatime products need to continue to innovate in creating new flavor variants and unique products to maintain their appeal amidst fierce competition. And continue to conduct market research periodically, to find out the developing trends. And maximize the use of social media for promotion and interaction with consumers, especially JKT48 fans.